2005
DOI: 10.1088/0957-4484/17/1/052
|View full text |Cite
|
Sign up to set email alerts
|

Ion irradiation induced structural modifications in diamond nanoparticles

Abstract: Structural modification of nanosized diamonds (ND) irradiated with 100 keV 15N ions for various doses was investigated using transmission electron microscopy (TEM) and Raman spectroscopy. Raman active modes showing a long-range order of diamond were observed for samples dosed with 1015 cm−2. However, the formation of a graphitic phase was observed, from TEM images, for ion doses as low as 1014 cm−2. The threshold dose for complete transformation of ND (sp3 to sp2) due to this implant is found to be greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…590 Ion irradiation has also been shown to be able to induce structural modifications in diamond nanoparticles. 617 The effects of irradiation on nanocluster thin films were studied by simulating the irradiation of porous nanocrystalline thin films with 5-30 keV Xe and Au ions. 618 It was reported that the films could be substantially densified by the irradiation while preserving nanocrystallinity.…”
Section: Phase Changes In Nanoparticlesmentioning
confidence: 99%
“…590 Ion irradiation has also been shown to be able to induce structural modifications in diamond nanoparticles. 617 The effects of irradiation on nanocluster thin films were studied by simulating the irradiation of porous nanocrystalline thin films with 5-30 keV Xe and Au ions. 618 It was reported that the films could be substantially densified by the irradiation while preserving nanocrystallinity.…”
Section: Phase Changes In Nanoparticlesmentioning
confidence: 99%
“…Therefore, the peak around 1547 cm À1 in Figure 4(c) is assigned to be the G band of graphite. The G peak is also associated with long-range order of sp 2 carbon [26]. Raman spectra corresponding to 5% and 10% hydrogen samples show a diamond peak at 1332 cm À1 and graphite peak at 1593 cm À1 , respectively.…”
Section: Methodsmentioning
confidence: 96%
“…On the other hand, N incorporation via ion implantation can modify the properties of nanodiamond through controlled doping. Ion implantation can also be used to tailor their sp 3 to sp 2 ratio for the diamonds or related carbon materials by properly selecting the dose and energy of implantation [14][15][16]. In this way, hybrid structures of sp 2 and sp 3 form of carbon such as graphite with NCD are formed which further extend the diversity of building units for the novel composites and other applications.…”
Section: Introductionmentioning
confidence: 99%